2009
DOI: 10.1002/ibd.20960
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the cannabinoid 2 receptor (CB2) protects against experimental colitis

Abstract: Background-Activation of cannabinoid (CB) 1 receptors results in attenuation of experimental colitis. Our aim was to examine the role of CB 2 receptors in experimental colitis using agonists (JWH133, AM1241) and an antagonist (AM630) in trinitrobenzene sulfonic acid (TNBS)-induced colitis in wildtype and CB 2 receptor-deficient (CB 2 -/-) mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
195
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 165 publications
(204 citation statements)
references
References 30 publications
7
195
1
1
Order By: Relevance
“…Recently, Gertsch et al 23 reported that BCP is a CB2 agonist. CB2 is expressed mainly in immune cells, and its activation limits intestinal inflammation 30 and reduces proinflammatory mediator release. 67 The present study demonstrated that the anti-inflammatory effect of BCP was almost completely reversed by the selective CB2 antagonist AM630, strongly suggesting that a great part of the anti-inflammatory properties of BCP observed in DSS-induced colitis was mediated by CB2 activation.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Gertsch et al 23 reported that BCP is a CB2 agonist. CB2 is expressed mainly in immune cells, and its activation limits intestinal inflammation 30 and reduces proinflammatory mediator release. 67 The present study demonstrated that the anti-inflammatory effect of BCP was almost completely reversed by the selective CB2 antagonist AM630, strongly suggesting that a great part of the anti-inflammatory properties of BCP observed in DSS-induced colitis was mediated by CB2 activation.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, CB 1 expression was increased in the myenteric plexuses of DNBS-mice, owing to an increase in cells expressing CB 1 , with no change in the overall neuronal population [50], whereas no difference was observed in CB 1 mRNA expression in the colon of TNBS-mice [57]. CB 2 expression, by contrast, was increased in one study of DSS-induced colitis and TNBS mice [61] but unchanged in a second study of TNBS mice [57].…”
Section: Reviewmentioning
confidence: 96%
“…AM1241 (10 mg/kg or 20 mg/kg, b.i.d. ), a CB 2 agonist, was used in the context of TNBS-induced colitis with the same outcome as JWH-133 [61]. The effects of both agonists were confirmed to be CB 2 -mediated because they were reversed in the presence of AM630 (10 mg/kg or 20 mg/kg, q.d.)…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…[7][8][9] The beneficial role of CB 2 in intestinal inflammation has been highlighted in several in vivo and in vitro studies. [10][11][12][13] Moreover, the genetic invalidation of FAAH in animals with 2,4-dinitrobenzene sulfonic acid (DNBS)-induced colitis significantly reduced tissue inflammation. 14 It has also been showed that URB597, a FAAH inhibitor, increased survival and decreased inflammation in mice suffering from trinitrobenzene sulfonic acid (TNBS)-induced colitis.…”
Section: C101 Conformationally Constrained Analogs Of 4-mentioning
confidence: 99%